A Model for Accounting Flexibility . - Tucker, Marvin W.; Tracy, John A. (The Accounting Review, 1971)
Abstract This article examines a proposed model for accounting flexibility. Mathematical models have been constructed to characterize many accounting problems. No less susceptible to modeling is the well-known phenomenon of flexibility of choice in the application of generally acceptable deterministic models to income measurement in identical or similar circumstances. Borrowing from the mathematics of combinatorics, one can calculate the congeries of different ways to determine net income implicit in the inventory of deterministic models available to a given entity. There are as many possible combination of income figures as there are different ways of applying the different deterministic models to the given measurement problems. One assumption interposed is that judgmental estimates of data, where applicable, would not vary among models. For example, estimate of useful life for fixed assets would not vary among different models. Only different mathematical operations are performed on the same data. Accounting flexibility represents the number of different ways to net income that the number of net income combinations equally competent accountants could take working with the same data for a given entity.